2021
DOI: 10.47577/biochemmed.v2i2.4328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Apricot and Apricot Kernels on Human Health and Nutrition: A Review of Recent Human Research

Abstract: Plants are one of the most important sources of medicine for humans to face diseases and disorders. Despite some advances in the field of allopathic system of medicine, adverse reactions have not been prevented from being an integral part of modern medicine. Plants are one of the important sources of drug discovery in both modern and traditional medicine systems worldwide. Recent developments in food and nutrition, consumer preferences shifted to foods rich in nutraceuticals. Furthermore 70% of marketed drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…In fact, it can exert different positive effects against such as cancer, cardiovascular disease, atherosclerosis and those diseases related to the aging. Furthermore, it can have protective effect on kidney and liver [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it can exert different positive effects against such as cancer, cardiovascular disease, atherosclerosis and those diseases related to the aging. Furthermore, it can have protective effect on kidney and liver [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Turkey is the world’s leading producer of apricots (127,328 tons) and produces approximately 22.9% of the world’s fresh apricots and nearly 68% of the world’s dried apricots [ 4 ]. According to available literature, it has been concluded that apricot kernels can also be utilized for thermal energy storage [ 5 ], traditional medicine [ 6 ], production or maintaining the quality of oils [ 7 ], cosmetic products [ 8 , 9 ], food products [ 10 ], and fabrication of antimicrobial film [ 11 ]. Especially in the food industry, apricot kernels along with skins are used in the formulation of bakery and confectionery products [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Alajil et al [ 16 ] reported that the maximum tolerance of amygdalin by human intravenous injection is approximately 0.07 g/kg, and interestingly, numerous studies revealed that bitterness is one of the major causes that restrict the industrial application and nutritional value of wild apricot kernels [ 5 ]. Despite the several benefits of the fruit, the apricot kernel comprises potential bioactive components and nutrients including carotenoids, carbohydrates, vitamins, phenols, terpenoids, esters, and volatile compounds [ 7 ]. The apricot kernel is also considered a promising ingredient in the health sector as it has anti-cancer, antioxidant, antimicrobial, antiasthma, inflammatory, atherosclerotic, anti-analgesic, and anti-hyperlipidemia properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations